Fatty acid distribution of cord and maternal blood in human pregnancy: special focus on individual trans fatty acids and conjugated linoleic acids - Enke, Uta (BioMed Central, 2011)
BACKGROUND: Maternal nutrition in pregnancy has a crucial impact on the development of the fetus. Dietary trans fatty acids (tFA) are known to have adverse health effects, especially during pregnancy. However, the distribution of tFA produced via partial hydrogenation of vegetable oils (mainly elaidic acid; t9) differs compared to ruminant-derived tFA (mainly vaccenic acid; t11). Recent findings indicate that they may have different impact on human health. Therefore, in this study, plasma and erythrocytes of mother-child pairs (n = 55) were sampled to investigate the distribution of tFA, including individual trans C18:1 fatty acids and conjugated linoleic acids (CLA) in fetal related to maternal lipids; with additional consideration of maternal dairy fat intake. RESULTS: Portion of t9 and t11, but also of c9,t11 CLA was higher in maternal than in fetal blood lipids. The portion of t9 in maternal and fetal lipids differed only slightly. In contrast, the portion of fetal t11 was only half of that in maternal blood. This led to a fetal t9/t11-index in plasma and erythrocytes being twice as high compared to the maternal values. A high dairy fat intake resulted in elevated portions of t11 and its Δ9-desaturation product c9,t11 CLA in maternal blood. In contrast, in the respective fetal blood lipids only c9,t11 CLA, but not t11 was increased. Nevertheless, a positive association between maternal and fetal plasma exists for both t11 and c9,t11 CLA. Furthermore, in contrast to t9, t11 was not negatively associated with n-3 LC-PUFA in fetal blood lipids. CONCLUSIONS: Fetal blood fatty acid composition essentially depends on and is altered by the maternal fatty acid supply. However, in addition to dietary factors, other aspects also contribute to the individual fatty acid distribution (oxidation, conversion, incorporation). The lower portion of fetal t11 compared to maternal t11, possibly results from Δ9-desaturation to c9,t11 CLA and/or oxidation. Based on the fatty acid distribution, it can be concluded that t11 differs from t9 regarding its metabolism and their impact on fetal LC-PUFA.